Needs Analysis And Design Of Gamification-Based Learning Management System Edukati To Support Flipped Classroom Of Cell Material - Yuanika, Aulia Hilma; Saiful Ridlo (Universitas Negeri Semarang, 2025)
The development of digital technology in the era of industrial revolution 4.0 towards society 5.0 demands biology learning that is more interactive, contextual, and relevant to the characteristics of 21st-century learners. However, high school biology teachers still face the challenge of low student understanding of abstract cell concepts, such as organelle structure-function relationships and cell division mechanisms. This material is often understood as rote, while learning media have not fully supported visualization or interactivity. The integration of the flipped classroom model with a gamification-based Learning Management System (LMS) is seen as a potential solution. This research aims to analyze the learning needs of cell concepts in high school and design a gamification-based LMS that is in accordance with the flipped classroom model. This study used an exploratory descriptive approach at the needs analysis stage involving 42 students of class XI MIPA and a biology teacher, which was then positioned as part of the planning stage in the Alessi & Trollip development model (RnD). The results of the needs analysis were then used as the basis for designing the initial design of the gamification-based LMS (design stage). The results of student needs show three aspects, namely the level of understanding of cell concepts is in the medium category (74.5%), while technology readiness (78.5%) and interest in flipped classroom (79.25%) are in the high category. Based on the needs analysis, the learning media were designed using Moodle “Edukati” LMS with gamification elements in the form of points, leaderboards, and multilevel challenges. The Understanding by Design (UbD) principle was used as a reference in formulating the integration of objectives, assessments, and learning activities. The results showed that the initial design of the gamification-based LMS has the potential to support the implementation of flipped classroom learning on cell material and is worth testing in the further development stage.